2018
DOI: 10.1111/nph.15037
|View full text |Cite
|
Sign up to set email alerts
|

A cytochrome P450 CYP71 enzyme expressed in Sorghum bicolor root hair cells participates in the biosynthesis of the benzoquinone allelochemical sorgoleone

Abstract: Summary Sorgoleone, a major component of the hydrophobic root exudates of Sorghum spp., is probably responsible for many of the allelopathic properties attributed to members of this genus. Much of the biosynthetic pathway for this compound has been elucidated, with the exception of the enzyme responsible for the catalysis of the addition of two hydroxyl groups to the resorcinol ring.A library prepared from isolated Sorghum bicolor root hair cells was first mined for P450‐like sequences, which were then analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Rice genome contains at least 356 P450 genes grouped into 10 different clans, and CYP71 clan is the largest set (Nelson and Werck-Reichhart, 2011; Nelson et al, 2004). In sunflowers and sorghum bicolor, several CYP71 members participated in the synthesis of eupatolide, inunolide and sorgoleone (Frey et al, 2018; Pan et al, 2018). In rice, eight CYP450 genes including three highly homologous proteins of CYP71 clan ( OsCYP71D8L, OsCYP71D8 and OsCYP71D7 ) are clustered as a tandem array on chromosome 2, but their characters and functions have been little known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice genome contains at least 356 P450 genes grouped into 10 different clans, and CYP71 clan is the largest set (Nelson and Werck-Reichhart, 2011; Nelson et al, 2004). In sunflowers and sorghum bicolor, several CYP71 members participated in the synthesis of eupatolide, inunolide and sorgoleone (Frey et al, 2018; Pan et al, 2018). In rice, eight CYP450 genes including three highly homologous proteins of CYP71 clan ( OsCYP71D8L, OsCYP71D8 and OsCYP71D7 ) are clustered as a tandem array on chromosome 2, but their characters and functions have been little known.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP71 clan is the largest set of P450s and represents more than half of all CYPs in higher plants (Nelson and Werck-Reichhart, 2011; Nelson et al, 2004). In plants, CYP71BL1, CYP71DD6 and CYP71AM1 are involved in the synthesis of eupatolide, inunolide, and sorgoleone, respectively (Frey et al, 2018; Pan et al, 2018). We previous showed that CYP71D8 was differentially expressed in two rice varieties under drought stress (Zhang et al, 2012), but the functions of CYP71 members remain unknown in rice.…”
Section: Introductionmentioning
confidence: 99%
“…The binary vectors for transient expression experiments (pLH‐Sorg, pLH‐G, pLH‐DES, pLH‐PQ, pLH‐GPQ and pLH‐PQD), as well as pCB404‐P19 (Pan et al ., 2018), were mobilized into the Agrobacterium tumefaciens strain EHA105 as described previously (Hofgen & Willmitzer, 1988). The cultures were maintained in LB (Luria‐Bertani) medium supplemented with appropriate antibiotics (25 mg l −1 rifampicin, 100 mg l −1 spectinomycin, and 300 mg l −1 streptomycin for strains harboring pLH vectors; 25 mg l −1 rifampicin, 300 mg l −1 streptomycin, and 50 mg l −1 kanamycin for the pCB vector).…”
Section: Methodsmentioning
confidence: 99%
“…The solution was heated at 100°C for 30 min and then cooled to room temperature. The silylated fractions were then analyzed by GC-MS according to previously described methods (Pan et al, 2018). Sorgoleone quantification was performed according to the methods described previously by Cook et al (2010).…”
Section: Gas Chromatography/mass Spectrometry (Gc/ms) Analysis Of Sormentioning
confidence: 99%
“…Increasing exploration of shallow soil by increasing root length density or by increasing root hair length and density might be beneficial for P capture. In addition, benefits from more root hairs of sorghum could come from their contribution to the synthesis and exudation of sorgoleone that have demonstrated roles in growth inhibition of weeds (Netzly & Butler 1986;Pan et al 2018).…”
Section: Introductionmentioning
confidence: 99%